2020
DOI: 10.3390/antiox9030252
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Constitution, Phytochemical and Macronutrient Content in Three Species of Microgreens as Modulated by Natural Fiber and Synthetic Substrates

Abstract: The present study examined the modulatory effects of natural fiber substrates (agave fiber, coconut fiber and peat moss) and synthetic alternatives (capillary mat and cellulose sponge) on the nutritive and phytochemical composition of select microgreens species (coriander, kohlrabi and pak choi) grown in a controlled environment. Polyphenols were analyzed by UHPLC-Q-Orbitrap-HRMS, major carotenoids by HPLC-DAD, and macro-minerals by ion chromatography. Microgreens grown on peat moss had outstanding fresh and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
62
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 55 publications
8
62
1
Order By: Relevance
“…Under amber lighting one half of the microgreens (MO, MR, MS, RR) showed moderate correlation (r = 0.48-0.58) while the other half (PC, MB, MG, RO) showed weak correlation (r = −0.3-0.28) ( Table 2). It is generally reported that blue light positively enhances phenolic content in vegetables and herbs like lettuce, tomato and basil (Johkan et al, 2010;Kim et al, 2013;Kyriacou et al, 2020). In our study, TPC was more strongly correlated to blue light than amber light as seen in MO, MR, MS, RR (r = 0.61-0.73), moderately in MG (r = 0.53) and generally the same in other microgreens (Table 2).…”
Section: Effects Of Lighting On Total Phytochemical Content Of Microgsupporting
confidence: 71%
“…Under amber lighting one half of the microgreens (MO, MR, MS, RR) showed moderate correlation (r = 0.48-0.58) while the other half (PC, MB, MG, RO) showed weak correlation (r = −0.3-0.28) ( Table 2). It is generally reported that blue light positively enhances phenolic content in vegetables and herbs like lettuce, tomato and basil (Johkan et al, 2010;Kim et al, 2013;Kyriacou et al, 2020). In our study, TPC was more strongly correlated to blue light than amber light as seen in MO, MR, MS, RR (r = 0.61-0.73), moderately in MG (r = 0.53) and generally the same in other microgreens (Table 2).…”
Section: Effects Of Lighting On Total Phytochemical Content Of Microgsupporting
confidence: 71%
“…Day/night temperatures and relative humidity were set at 24/18 ± 1 • C and 60%/70%, respectively. Microgreens species were grown in trays (56 × 37 × 5.5 cm: W × L × D) filled with peat moss substrate (pH 6.3 and electrical conductivity 0.2 dS m −1 ; Special Mixture, Floragard Vertriebs-GmbH, Oldenburg, Germany) and fertigated daily with a quarter-strength modified Hoagland solution described in detail in Kyriacou et al [15].…”
Section: Genetic Materials and Climate Chamber Conditionsmentioning
confidence: 99%
“…Indeed, microgreens enclose a greater load of essential phytonutrients compared to their mature counterparts [3,4,6,10,13]. Suchlike dense phytochemical composition has garnered the attention of nutrition researchers [6,15] and gained them prevalence among food technologists, urban farmers, and consumers [15]. As public concern about environmental and nutritional aspects of food production has recently arisen [16,17], consumers are orienting their purchasing behavior toward healthier and environmentally friendlier food products [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Microgreens can be considered as a functional food due to their high content in several healthy compounds for humans [8][9][10][11][12][13][14][15]. This emerging category of vegetable products can be defined as immature greens, which are harvested when the cotyledon leaves have fully developed and the first true leaves have emerged, although the term 'microgreens' lacks any legal definition [16].…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have been carried out regarding the nutritional evaluation of microgreens [8,9,11,13,15,[22][23][24], only one reports the nutritional ranking of some microgreens on the basis of an index that is able to summarize the overall nutritional quality [14]. At the same time, the literature lacks research into the adoption of this evaluation method to be used not only to compare different genotypes but also to assess the effects of growing conditions on the microgreens' nutritional quality.…”
Section: Introductionmentioning
confidence: 99%